Pro NetBeans IDE 6 rich client platform edition - Myatt, Adam (Apress, 2008)
Provides information on building client/Internet applications using the NetBeans IDA platform.
Keywords: Computer programming; Java (Computer language); Java (Computer program language); NetBeans Platform 6